An exploration of reflective practice in security risk management: how senior security managers experience reflective practice. Issue 4 (4th July 2018) - Hasenstab, Alexander Nikolaus
ABSTRACT: This study explored how senior security risk managers experience reflective practice. It looked specifically at the extent to which the practitioners reflected on their own practice, the ways in which they did so, and the usefulness of reflective practice for security risk management managers. Grounded theory methodology was used to collect and analyse relevant data. The outcome of the study is two-fold. From a theoretical perspective, the study provides a substantive theory about how senior security risk management practitioners experience reflective practice. From a professional practice angle, the study offers essential functional information about reflective practice in security risk management.